2015
DOI: 10.1002/etc.3016
|View full text |Cite
|
Sign up to set email alerts
|

Natural organic matter–induced alleviation of the phytotoxicity to rice (Oryza sativa L.) caused by copper oxide nanoparticles

Abstract: Natural organic matter (NOM) can interact with engineered nanoparticles (NPs) in the environment and modify their behavior and toxicity to organisms. In the present study, the phytotoxicity of copper oxide (CuO) NPs to rice seedlings in the presence of humic acid as a model NOM was investigated. The results showed that CuO NPs induced the inhibition of root elongation, aberrations in root morphology and ultrastructure, and losses of cell viability and membrane integrity. The adverse effects partly resulted fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 46 publications
1
29
0
Order By: Relevance
“…The roots assayed had been rinsed only with deionized water, to avoid tissue damage and leakage occurring with more rigorous cleaning methods. Despite not distinguishing between Cu physically associated with the roots, such as agglomerates on root hairs (Adams et al 2017) and within root cells, the concentration of Cu associated with the roots was orders of magnitude higher than in the shoots, implying control of translocation of Cu within the plant, as reported by Gao et al (2018) for wheat and in rice (Peng et al 2015(Peng et al , 2017. In the present study, only the control showed greater accumulation of Cu in the shoots than roots, with a shoot to root ratio >1; all doses of CuONPs resulted in partial exclusion of Cu partitioned into shoots (shoot/root >1; Figure 1E).…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…The roots assayed had been rinsed only with deionized water, to avoid tissue damage and leakage occurring with more rigorous cleaning methods. Despite not distinguishing between Cu physically associated with the roots, such as agglomerates on root hairs (Adams et al 2017) and within root cells, the concentration of Cu associated with the roots was orders of magnitude higher than in the shoots, implying control of translocation of Cu within the plant, as reported by Gao et al (2018) for wheat and in rice (Peng et al 2015(Peng et al , 2017. In the present study, only the control showed greater accumulation of Cu in the shoots than roots, with a shoot to root ratio >1; all doses of CuONPs resulted in partial exclusion of Cu partitioned into shoots (shoot/root >1; Figure 1E).…”
Section: Resultsmentioning
confidence: 89%
“…Copper is sequestered in vacuoles of the root cells (Clemens et al ) as an exclusion strategy (Baker ). The observed binding of Cu to root cell walls also would limit Cu flux to the shoots (Kopittke et al , ; Peng et al ; Meychik et al ). The translocation of intact CuONPs with subsequent dissolution of CuONPs in planta also, however, is a potential mechanism for increased uptake into the shoot (Wang et al ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The currently available technology affords several approaches to increasing crop production and crop nutraceutical quality. One of these is the application of nanotechnology to improve productivity [4,5]. In recent years, nanotechnology has been used by means of the application of nanomaterials such as nanofertilizers, nanoparticles, or nanopesticides for nutrient management, genetic improvement, plant disease treatment, and plant growth promotion [4].…”
Section: Introductionmentioning
confidence: 99%